Nutrition Data Use and Needs: Findings from an Online Survey of Global Nutrition Stakeholders (P22-003-19). (13th June 2019) - Buckland, Audrey; Aung, Tricia; King, Shannon; Manorat, Renee; Becker, Laura; Piwoz, Ellen; Rawat, Rahul; Heidkamp, Rebecca; Thorne-Lyman, Andrew
Abstract: Objectives: There is a growing global demand for information to track nutritional status and its determinants, including intervention coverage. We developed an online survey to identify which nutrition indicators and data sources the global nutrition community uses currently and what information gaps remain. Methods: We created the survey using Qualtrics software and distributed it through multiple online nutrition-focused listservs and professional networks. Respondents were asked about their professional background, use of nutrition indicators in previous year, sources of accessed data, unfilled data needs, and how they used data in their work. Data were collected from July 16 to August 16 2018. Results were tabulated using Stata Version 14.0. Results: A total of 264 survey responses were received, 235 with responses beyond identifiers. The majority of stakeholders were from NGO and research communities. Two-thirds reported using data to make monitoring and evaluation decisions (Table 1). Demographic Health Surveys (DHS) were the most accessed national data source in the past year (74%), followed by the Multiple Indicator Cluster Surveys (42%) (Table 2). When data sources were stratified by respondent geographic focus area (single country vs. multi-country), 60% of stakeholders with a single country focus and 85% of stakeholders with a multi-country focus accessed the DHS. Among stakeholders who accessed aggregated data sources, most accessed the Global Nutrition Report (75%). The majority of respondents accessed or used at least one nutrition coverage or utilization indicator in the last 12 months (97%) including iron and folic acid supplementation for pregnant or lactating women (54%) (Figure 1). Several challenges to accessing and using data were identified such as data sometimes or frequently not being available at the geographical level needed (82%) or being out of out-of-date (77%) (Figure 2). Conclusions: High-quality, actionable nutrition data are needed to understand progress towards reducing malnutrition and reaching global nutrition targets. Effective monitoring of progress in nutrition requires data that are accessible to decision makers who assess programs and allocate resources. Funding Sources: Bill & Melinda Gates Foundation. Supporting Tables, Images and/or Graphs: